Standardizing the creative imagination scale (CIS) on undergraduate psychology students at the University of Stelllenbosch - Van Niekerk, Rethea Suzanne (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1999.